Soft and Stretchable Liquid Metal Composites with Shape Memory and Healable Conductivity - Bhuyan, Priyanuj; Wei, Yuwen; Sin, Dongho; Yu, Jaesang; Nah, Changwoon; Jeong, Kwang-Un; Dickey, Michael D.; Park, Sungjune (American Chemical Society, 2021)
Shape memory composites are fascinating materials with the ability to preserve deformed shapes that recover when triggered by certain external stimuli. Although elastomers are not inherently shape memory materials, the inclusion of phase-change materials within the elastomer can impart shape memory properties. When this filler changes the phase from liquid to solid, the effective modulus of the polymer increases significantly, enabling stiffness tuning. Using gallium, a metal with a low melting point (29.8 degrees C), it is possible to create elastomeric materials with metallic conductivity and shape memory properties. This concept has been used previously in core-shell (gallium-elastomer) fibers and foams, but here, we show that it can also be implemented in elastomeric films containing microchannels. Such microchannels are appealing because it is possible to control the geometry of the filler and create metallically conductive circuits. Stretching the solidified metal fractures the fillers; however, they can heal by body heat to restore conductivity. Such conductive, shape memory sheets with healable conductivity may find applications in stretchable electronics and soft robotics.
Keywords: STIFFNESS; DESIGN; SENSOR